Africa’s agricultural research pool - Beintema, Nienke M.; Stads, Gert-Jan; Flaherty, Kathleen (International Food Policy Research Institute, 2014)
Absolute levels of staffing in public agriculture research and development (R&D) vary considerably across the 39 countries in Africa south of the Sahara participating in the Agricultural Science and Technology Indicator (ASTI) survey (Map 1). In 2011, Ethiopia, Ghana, Kenya, Nigeria, South Africa, Sudan, and Tanzania each employed more than 500 full-time equivalent (FTE) researchers. In contrast, 11 countries employed fewer than 100 FTE researchers each.1 Despite recent challenges, many western African countries have maintained relatively large pools of well-qualified researchers (those holding PhD and MSc degrees) (Map 2). In contrast, less than half of researchers in Botswana, the Democratic Republic of the Congo, Eritrea, Ethiopia, Guinea, Guinea-Bissau, Lesotho, Liberia, Mozambique, and Zimbabwe hold graduate degrees.